Study on Dynamic Behavior Law and Microseismic Monitoring in Stoping Process of Roadway with High Gas and Wide Coal Pillar - Baobin Gao; Chuangnan Ren; Qun Dong; Liwei Chen (Shock and Vibration, 2021)
In order to study the dynamic characteristics and microseismic distribution in the mining process of roadway with high gas and wide coal pillar, combined with the two dynamic events of N2105 working face in Yuwu Coal Industry, theoretical analysis and field measurement research were carried out. According to the theory of structural mechanics and geomechanics, the causes of dynamic appearance are analyzed. Combined with the specific situation, the influence of mining depth, coal pillar width, gas pressure, and content on the dynamic performance is analyzed. Stress monitoring and microseismic monitoring are carried out on one side of coal seam. The results show that, with the increase of the mining distance, the backside roof of the goaf is prone to unbalanced fracture due to the lack of lateral stress, and the impact pressure generated is used for the reserved protective coal pillar behind the goaf, causing the floor heave of coal seam. The combined stress generated by the anticlinal structure below the working face interacts with the abutment pressure of the working face to produce superposition effect, which promotes the occurrence of dynamic appearance. The critical depth of rock burst in Yuwu Coal Industry is about 600m. The increase of coal elastic energy caused by roof subsidence is more uniform with the increase of coal pillar width. The decrease of gas pressure in coal seam promotes the rock burst disaster. The vertical stress of coal seam at one side of the working face shows different evolution characteristics along the trend and strike. The vertical stress of coal seam in the lateral range of 53 m is adjusted to different degrees and tends to be stable until 300 m behind the working face. The active microseismic area in the middle of the working face was located 50 m in front of the working face, and the microseismic activity continued to 30–50 m behind the working face. The active microseismic area at the side of the roadway was located 30 m in front of the working face, and the microseismic activity continued to 100–180 m behind the working face. The inflection point, where the stress in the elastic area of coal pillar increases sharply, corresponds to the active microseismic area, which indicates that the dynamic characteristics in the mining process of roadway with high gas and wide coal pillar are related to the distribution law of microseismic. This study has a certain guiding significance for optimizing the width of reserved coal pillar, monitoring the coal seam stress/microseismic, and understanding the dynamic disaster of coal and rock under complex conditions.